PENGARUH PEMBERIAN TERAPI JUS WORTEL TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI RW. 018 KEL. MEKARJAYA KEC. SUKMAJAYA KOTA DEPOK TAHUN 2012 - Sari, Anggi Puspita; Herlina, Santi (Fakultas Ilmu Kesehatan, 2014)
Hypertension is one of the deadliest diseases in the world which is often called the silent killer. The disease is dangerous because it deals with the cardiovascular, circulatory system is functioning to provide and circulate oxygen supply and nutrients to all tissues and organs are needed in the process of metabolism. Even the estimated number of people with hypertension will increase to 1.6 billion by 2025. This study aims to determine the effect of carrot juice therapy to decrease blood pressure in hypertensive patients. This Quasi-experimental study used a sample of 20 respondents, each intervention group and control group 10 respondents. Data collected and analyzed to meet the criteria using univariate and bivariate using T-test, which consists of test Paired Samples T-test and Independent t-tests. The results showed that there is influence of carrot juice therapy to decrease blood pressure in hypertensive patients, with a value of p = 0.000 for systolic and p-value = 0.001 for diastolic (p-value < 0.05). The results also indicate that there are significant differences between blood pressure reduction in the intervention group and control group (p-value < 0.05). This research is expected to be useful as an input to the world of nursing, family, and especially the client to learn more about nonpharmacological treatment of blood pressure reduction.